Long Coronavirus Disease and Chronic Coronavirus Disease in Health-Care Workers: A Cross-Sectional Study - Çulpan, Hazal Cansu; Aydın, Sümeyye Nur; Can, Günay; Fenercioğlu, Ayşen Kutan; Erginöz, Ethem (Cerrahpaşa Medical Journal, 2024)
Objective: Recent studies on coronavirus disease 2019 (COVID-19) reported that symptoms persisted for weeks or even months in some patients and they are called long COVID, post-acute COVID-19, etc. The aim of this study is to examine the frequency of long COVID in health-care workers, identify the common symptoms, and assess the possible factors that may be associated. Methods: In this cross-sectional study a self-administered questionnaire was carried out. About half (48.1%) of the 131 participants evaluated had long COVID. The 41.3% of long COVID cases had chronic COVID. Results: The percentage of those who were hospitalized in inpatient clinics or intensive care units during infection was higher in long COVID patients (31.7% vs. 14.3%) as well as frequency of oxygen need (36.5% vs. 17.9%). Fatigue was the most frequent symptom (54%), followed by myalgia (47.6%) and arthralgia (42.9%). Conclusion: The study showed that approximately half of health-care workers who had COVID-19 suffer from long COVID. Cite this article as: Çulpan HC, Aydın SN, Can G, Kutan Fenercioğlu A, Erginöz E. Long COVID and chronic COVID in health-care workers: A cross-sectional study. Cerrahpaşa Med J. 2024;48(1):88-92.